Outcomes of civilian pediatric craniocerebral gunshot wounds: A systematic review. Issue 6 (December 2020) - Duda, Taylor; Sharma, Arjun; Ellenbogen, Yosef; Martyniuk, Amanda; Kasper, Ekkehard; Engels, Paul T.; Sharma, Sunjay
Abstract : BACKGROUND: Pediatric craniocerebral gunshot injuries (CGIs) occur both in the context of accidental and intentional trauma. The incidence and physiology of pediatric CGIs merit reexamination of prognostic factors and treatment priorities. This study characterizes the current understanding of mortality and prognostic factors in this patient population. METHODS: A systematic search was conducted. Selection criteria included all studies published since 2000, which described civilian isolated CGIs in pediatric patients. Data were analyzed qualitatively and quantitatively to identify factors prognostic for the primary outcome of mortality. Secondary outcomes included functional outcome status, requirement for surgery, and injury complications. Study quality was assessed with the Newcastle-Ottawa Scale. This study was registered with PROSPERO (CRD42019134231). RESULTS: Initial search revealed 349 unique studies. Forty underwent full text screening, and eight studies were included in the final synthesis. The overall mortality rate was 44.8%. Most CGIs occurred in older teenagers. Aggressive surgical treatment was recommended by one author, while remaining studies emphasized clinical judgment. Reported prognostic factors include initial Glasgow Coma Scale, pupil reactivity, involvement of multiple lobes or deep nuclei, and bihemispheric injuries. Reported complications from CGIs included seizure, meningitis, abscess, cerebrospinal fluid leak, bullet migration, focal neurological deficits, endocrine abnormalities, cognitive deficits, and neuropsychological deficits. The Glasgow Outcome Scale was the predominant measure of function and demonstrated a moderate recovery in 17.4% and a good recovery in 27.3% of patients. CONCLUSION: This systematic review analyzed the existing evidence for prognostic factors in the context of pediatric CGIs. Significant long-term clinical improvement is possible with interventions including urgent surgical therapy. Fixed bilateral pupils and low initial Glasgow Coma Scale correlate with mortality but do not predict all patient outcomes. Patients younger than 15 years are underreported and may have differences in outcome. The literature on pediatric CGIs is limited and requires further characterization. LEVEL OF EVIDENCE: Systematic Review, level IV.